Analisis Pengaruh Profitabilitas, Solvabilitas, Likuiditas, Ukuran Perusahaan, dan Reputasi Auditor Terhadap Audit Report Lag pada Perusahaan Sektor Properti yang Terdaftar di BEI Periode 2021-2023 - Shima Pungkas Yudhasmara; Lilik Pujiati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the influence of profitability, solvency, liquidity, company size and auditor reputation on audit report lag in property sector companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period. Audit report lag is the time lag between the end of the fiscal year and the publication of the audit report, which can affect investor confidence and the effectiveness of the capital market. The research method used is a quantitative approach with multiple regression analysis techniques. The research results show that profitability has a negative and significant influence on audit report lag, which means that the higher the company's profitability, the faster the audit report is issued. Meanwhile, solvency, liquidity, company size and auditor reputation do not have a significant influence on audit report lag. These findings indicate that profitability is the main factor in determining the speed of audit completion, while other factors do not directly influence the delay in publishing the audit report. This research provides implications for companies, auditors and stakeholders to pay more attention to profitability aspects in managing the timeliness of financial reporting.